Heart Failure With Mid-range Ejection Fraction: Every Coin Has Two Sides - Zhu, Kaiyuan; Ma, Teng; Su, Yang; Pan, Xin; Huang, Rongrong; Zhang, Fenglei; Yan, Chunxi; Xu, Dachun (Frontiers in Cardiovascular Medicine, 2021)
This review summarizes current knowledge regarding clinical epidemiology, pathophysiology, and prognosis for patients with HFmrEF in comparison to HFrEF and HFpEF. Although recommended treatments currently focus on aggressive management of comorbidities, we summarize potentially beneficial therapies that can delay the process of heart failure by blocking the pathophysiology mechanism. More studies are needed to further characterize HFmrEF and identify effective management strategies that can reduce cardiovascular morbidity and mortality of patients with HFmrEF.